Perancangan Aplikasi E-Commerce Koperasi Konsumen PC Nahdlatul Ulama Karawang - Ahmad Abdul Jabbar; Candra Galang Gemilang Putra; Wahyudin Wahyudin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
After the Covid-19 pandemic which has an impact on the instability of all sectors, including the economic sector. With regard to the impact caused by the Nahdlatul Ulama Karawang PC Consumer Cooperative, which is engaged in distribution and retail under the Nahdlatul Ulama Karawang Economic Institute, it also feels the impact of the Covid-19 pandemic. Creativity and the latest innovations are needed in increasing the productivity of the company. So the purpose of this research is to create an Android-based e-marketplace that is easier to use by today's society. In this study used a research method that is RnD (Research and Development). The stages that must be passed with this method start from analyze, design, development, implement and evaluate. The result of this research is the design of an android-based application and serves as a place for buying and selling online between the customer and the company. The test results of this application show that all the functions of the application can run well according to the needs of its users.